English teachers’ attitudes towards and experiences on the use of music to support teaching - Mansoniemi, Neea (My University, 2024)
The aim of this Minor Subject Thesis is to understand reasons behind English teachers’ experiences and attitudes considering the use of music for teaching purposes and to discover in which ways they have used music during their English lessons. The research has shown there is a positive impact of music and song lyrics for language learning and diverse aspects of it, motivation and long-term learning. This study examined 31 teachers’ attitudes, experiences and ways to use music in English teaching. A Webropol questionnaire was distributed via email to various institutions in Western and Southern Finland in April 2023. The questionnaire included both Likert scales and open-ended questions. The questions were analyzed both quantitatively and qualitatively, but the main focus was on qualitative analysis in this mixed-methods study. Based on the analysis, the teachers’ attitudes considering the topic were mostly positive. The findings showed that the teachers utilize songs in various ways teaching topics like verb tenses, vocabulary, pronunciation and cultural elements. The biggest limitations were the lack of teaching material that involves music and the lack of time to prepare lessons that involve music, including finding a suitable song and creating the teaching material. In the future, the study could be repeated with a higher number of participants and, possibly, study separately teachers that teach different language levels. This way, more information could be obtained from different age groups. Another possibility would be to use the learners themselves as a study group instead of the teachers.
Keywords: music, song lyrics, motivation, English, language learning, language teaching